Estrategias de comercialización en el cyber y papelería “El Parke” en el periodo 2022. - Suñiga Murillo, Matilde Sulema (2023)
Marketing is defined as a set of initiatives and activities designed to drive sales and ensure that a product or service ultimately reaches the consumer. The creation of effective marketing strategies is essential to capture the attention and preference of customers. The objective of this study is to learn about the marketing and commercialization strategies in Cyber y Papelería "El Parke" and how they affect it, thus showing the potential long-term impacts in terms of the lack of design and implementation of advertising techniques or commercial strategies, which are essential to strengthen the presence of the business in the canton Baba and reach a wider audience. A descriptive research methodology was used, accompanied by an interview and a survey as tools for an analysis and scope of results according to the problems studied; therefore, a qualitative research approach was used, also considering the deductive and bibliographic methods. The results enunciated that the business does not have effective marketing strategies and does not make use of digital marketing. As a conclusion, it is argued that the absence of a marketing plan and commercialization strategies by Cyber y Papelería "El Parke" could have long-term negative repercussions for the business and the importance of implementing marketing plans in order to avoid the loss of recognition and market share is highlighted.